Degradação ruminal de silagem de capim-elefante com adição de vagem de algaroba triturada - do Rego, Anibal Coutinho [UNESP]; de Aguiar Paiva, Paulo Cesar; Muniz, Joel Augusto; Castello Branco Van Cleep, Eric Haydt [UNESP]; Machado Neto, Otavio Rodrigues (Univ Federal Ceara, Dept Geol, 2011)
This research was carried out to evaluate the ruminal degradation of dry matter (DM), crude protein (CP) and neutral detergent fiber (NDF) of silages of elephant grass (Pennisetum purpureum) cutting in 70; 90 and 110 days after regrowth with inclusion of 0; 5; 10 and 15% of mesquite (Prosopis juliflora) meal, based on natural matter in a completely randomized design, in split plot arrangement. Samples of silages were incubated in the rumen of two Jersey cows for 3; 6; 12; 24; 48; 72 and 96 h, and the bags at time "zero" were only washed with water to determine the soluble fraction. There was not interaction (P> 0.05) incubation time x inclusion of mesquite pods x cutting age of the grass for DM degradability, there was only interaction (P <0.05) between these factors for CP and NDF degradability. The most effective DM degradability (42.54%) was observed for 15% inclusion of mesquite pods. The effective CP degradability was higher (69.04%) for elephant grass silage with 70 days after regrowth with 15% of mesquite pods. The inclusion of mesquite pods in elephant grass silages improve DM, CP and NDF degradability, while increment of the age after regrowth result in reduction of this parameters.
Ruminal degradation of elephant grass silage with mesquite pods
Keywords: In situ degradability; Ensilage; Pennisetum purpureum; Prosopis juliflora